Les enjeux socio-environnementaux du développement durable en Amérique du Sud. Considérations à partir du cas colombien - Oscar Navarro (Développement Durable et Territoires)
Talk about sustained development in emergent countries such as in Latin America and specifically Colombia, implies to tackle the conflicting character linked to the possibility to aim the objectives of this development paradigm. It is so necessary to know socio-political and cultural obstacles these societies meet (corruption and institutional instability, armed conflict, poverty, etc…). Study socio-environmental conflict’s bases and psychosocial dynamics help to better understand these obstacles, but also to find out answers to better manage this pressure. Colombia’s case and water conflicts in the “Sierra de Santa Marta” above all will allow us to give an illustration of this matter.